Analisis Pengaruh Kualitas Pelayanan, Kepercayaan, Perceived Value dan Kepuasan Mahasiswa terhadap Loyalitas Mahasiswa - Dewi Murtiningsih; Widi Wahyudi (Neolectura, 2021)
This study aims to determine the effect of service quality on student loyalty; To determine the effect of trust on student loyalty; To determine the perceived value of student loyalty; To determine the effect of student satisfaction on student loyalty; To determine the effect of service quality, trust, perceived value of student satisfaction on student loyalty. This research is included in the type of explanatory research. The sample in this study amounted to 100 students. Questionnaires were used as a tool to collect respondent data, which were then tested using validity and reliability tests. The analytical tool used is linear regression analysis with SPSS Version 21 software. The results show that service quality has no effect on student loyalty, trust has no effect on student loyalty, perceived value has no effect. on student loyalty, student satisfaction affects student loyalty, and to know simultaneously service quality, trust, perceived value and student satisfaction affect student loyalty.